Portable literature : Reading, reacting, writing - Kirszner, Laurie G. (Cengage Learning, 2024)
This book is a highly accessible anthology that offers a broad selection of contemporary and classic, time-tested readings, along with introductions to literary genres, helpful study questions, prompts, and a down-to-earth guide to writing about literature.